2013
DOI: 10.1158/1535-7163.mct-12-0869
|View full text |Cite|
|
Sign up to set email alerts
|

Dual Programmed Cell Death Pathways Induced by p53 Transactivation Overcome Resistance to Oncolytic Adenovirus in Human Osteosarcoma Cells

Abstract: Tumor suppressor p53 is a multifunctional transcription factor that regulates diverse cell fates, including apoptosis and autophagy in tumor biology. p53 overexpression enhances the antitumor activity of oncolytic adenoviruses; however, the molecular mechanism of this occurrence remains unclear. We previously developed a tumor-specific replication-competent oncolytic adenovirus, OBP-301, that kills human osteosarcoma cells, but some human osteosarcoma cells were OBP-301-resistant. In this study, we investigate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 48 publications
3
54
0
Order By: Relevance
“…As viruses have developed sophisticated machineries to evade apoptotic cell death and interfere with ER stress and autophagy responses for their survival, 102,103 ICD may have played an essential role in the everlasting war between viruses and their hosts. We and other groups have found that many oncolytic viruses can induce apoptotic cell death and/or necrosis in cancer cells, 9,104,105,106 supporting their immunostimulatory potential to augment antitumor efficacy (Tables 4 and 5). 107,108 CVB3 infection induces multiple DAMPs including ecto-CRT, HMGB1 translocation from nuclei, and ATP release from human lung cancer cells.…”
Section: Damps Induced By Infection With Oncolytic Virusesmentioning
confidence: 77%
See 1 more Smart Citation
“…As viruses have developed sophisticated machineries to evade apoptotic cell death and interfere with ER stress and autophagy responses for their survival, 102,103 ICD may have played an essential role in the everlasting war between viruses and their hosts. We and other groups have found that many oncolytic viruses can induce apoptotic cell death and/or necrosis in cancer cells, 9,104,105,106 supporting their immunostimulatory potential to augment antitumor efficacy (Tables 4 and 5). 107,108 CVB3 infection induces multiple DAMPs including ecto-CRT, HMGB1 translocation from nuclei, and ATP release from human lung cancer cells.…”
Section: Damps Induced By Infection With Oncolytic Virusesmentioning
confidence: 77%
“…However, there are only two reports showing that virus-induced ecto-CRT was correlated with enhanced intratumoral infiltrations of immune subpopulations, which accounted for the 'in vivo' remarkable antitumor immunity. 9,65 Several studies showed that recombinant oncolytic adenoviruses induced ACD in human malignant glioma cells, 120 brain tumor stem cells, 121 osteosarcoma cells, 105 and lung cancer cells. 122 Newcastle disease virus also triggered autophagy in glioma cells to promote its viral replication.…”
Section: Different Types Of Immunogenic Cancer Cell Death H Inoue Andmentioning
confidence: 99%
“…Previous studies analyzed the role of p53 in replication-competent Ad, which harbored the p53 gene in the same Ad construct and consequently induced p53 expression in coordination with the viral replications. [14][15][16] In contrast to the present study, these reports demonstrated that expression of p53 augmented viral replications or release of viral AsPC-1 cells were uninfected or infected with Ad5-LacZ, Ad5-p53, AdF-Sur, AdF-MK, (3000 vp per cell) or in combination with Ad5-p53 and AdF-Sur or AdF-MK as indicated (3000 vp per cell for respective Ad) and the cell cycle progressions were analyzed with flow cytometry. Average and s.e.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 These studies did not analyze whether the combinatory effects were additive or synergistic in the cytotoxicity. The experimental systems of the previous studies were not the same as the present study in terms of p53 transduction.…”
Section: Discussionmentioning
confidence: 99%
“…With the advancement of radical surgery and neoadjuvant chemotherapy, the survival rates of osteosarcoma patients have dramatically improved in recent decades [3-6]. However, more than 20% of osteosarcoma patients die from tumor recurrence or metastasis, which remain major obstacles in bone cancer treatment [3, 7].…”
Section: Introductionmentioning
confidence: 99%